Effectiveness of dispatcher training in increasing bystander chest compression for out‐of‐hospital cardiac arrest patients in Japan. Issue 4 (7th August 2017) - Tsunoyama, Taichiro; Nakahara, Shinji; Yoshida, Masafumi; Kitamura, Maki; Sakamoto, Tetsuya
Abstract : Aim: The Japanese government has developed a standardized training program for emergency call dispatchers to improve their skills in providing oral guidance on chest compression to bystanders who have witnessed out‐of‐hospital cardiac arrests (OHCAs). This study evaluated the effects of such a training program for emergency call dispatchers in Japan. Methods: The analysis included all consecutive non‐traumatic OHCA patients transported to hospital by eight emergency medical services, where the program was implemented as a pilot project. We compared the provision of oral guidance and the incidence of chest compression applications by bystanders in the 1‐month period before and after the program. Data collection was undertaken from October 2014 to March 2015. Results: The 532 non‐traumatic OHCA cases were used for analysis: these included 249 cases before and 283 after the guidance intervention. Most patients were over 75 years old and were men. After the program, provision of oral guidance to callers slightly increased from 63% of cases to 69% ( P = 0.13) and implementation of chest compression on patients by bystanders significantly increased from 40% to 52% ( P = 0.01). Appropriate chest compression also increased from 34% to 47% ( P = 0.01). In analysis stratified by the provision of oral guidance, increased chest compressions were observed only under oral guidance. Conclusions: We found increased provision of oral guidance by dispatchers and increased appropriate chest compressions by bystanders after the training program for dispatchers had been rolled out. Long‐term observation and further data analysis, including patient outcomes, are needed. Abstract : After the standardized training program for dispatchers, cases of implementation of chest compressions by bystanders and appropriate chest compressions significantly increased. Cases of chest compressions and appropriate chest compressions increased only under oral guidance.